A linguagem do Caretas : um olhar entrecruzado - Torres Neto, Blás (2014)
The aim of this work is a reflective reading in the light of certain sciences and disciplines of rock carvings found in an archaeological site located in Itacoatiara (AM) on the banks of Urubu river, made by indigenous cultures that settled most likely near these historical records. Research leave comments on the various forms of representations of prints known as "straight", trying to relate them as manifestations of a striking visual language of the traditions left by visitors or inhabitants of that locality and use an authoritative look crisscrossed by Archaeology, Rock Art, Ethnolinguistic, Ethnoarchaeology, Iconography, Iconology and Semiotics as a theoretical model in order to recover and value the Amazon archaeological heritage. Keywords: Engraving Cave; Records; Art; Heritage; Culture.